2017
DOI: 10.1111/iju.13424
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in renal cell carcinoma: An analysis of Hispanic patients in a single‐payer healthcare system

Abstract: Within an equal access healthcare system, Hispanics seem to be diagnosed at younger ages, to have greater comorbidities and to present more frequently with clear cell renal cell carcinoma compared with non-Hispanic white patients. Despite lower stage and greater receipt of surgery, Hispanic ethnicity seems to be an independent predictor of mortality. Further work is necessary to confirm these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 26 publications
(38 reference statements)
1
24
0
8
Order By: Relevance
“…These findings are in concordance with prior studies about RCC in HAs. 5,12 Although the analysis results should be treated with caution owing to small sample size, we also found similar characteristics in the NA patients, such as younger age of diagnosis, higher frequency of ccRCC, and higher prevalence of diabetes than EA patients. Moreover, our results suggest that race/ ethnicity and obesity are risk factors independently associated with increased odds of RCC diagnosis at a younger age (< 50 years).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…These findings are in concordance with prior studies about RCC in HAs. 5,12 Although the analysis results should be treated with caution owing to small sample size, we also found similar characteristics in the NA patients, such as younger age of diagnosis, higher frequency of ccRCC, and higher prevalence of diabetes than EA patients. Moreover, our results suggest that race/ ethnicity and obesity are risk factors independently associated with increased odds of RCC diagnosis at a younger age (< 50 years).…”
Section: Discussionsupporting
confidence: 63%
“…4 One study also indicated that HAs appeared to be diagnosed at younger ages, have greater comorbidities, and present more frequently with clear-cell renal cell carcinoma (ccRCC) compared with EA patients. 5 Furthermore, it is well-known that in the United States, access to health care varies significantly by racial/ethnic groups, and this may explain the differences in cancer-related outcomes owing to treatment barriers. [6][7][8][9]…”
Section: Introductionmentioning
confidence: 99%
“…16 A study from Texas showed that ccRCC was very common among HAs, 17 but in the study from northern California, the frequencies of ccRCC were similar between HAs and NHWs. 33 RCC histologic subtypes may have several implications in treatment and prognosis, which play a role in preoperative counseling. It has been reported that ccRCC is more likely to present with advanced T stage, metastatic disease, and higher grade, and therefore patients with ccRCC tend to have a worse prognosis than patients with other histologic subtypes of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…These seven variables have been proposed in earlier models for the prediction of postoperative recurrence risk of patients diagnosed with RCCC [21] 23, and are also consistent with the main prognostic factors of CCRC. The difference of race has also been shown to be strongly predictive of evaluation risk after radical nephrectomy [22], but according to AIC analysis, the model including race exhibited weaker performance.…”
Section: Discussionmentioning
confidence: 99%